Liver Transplantation for Acute Liver Failure due to Mushroom Poisoning - Hayri Canbaz; Attila Bestemir; Sami Akbulut; Sezai Yilmaz; Yusuf Yavuz (The Turkish Journal of Gastroenterology)
Background/Aims: Liver transplantation is a life-saving approach in some cases of mushroom poisoning, which is one of the important causes of acute liver failure. However, debate continues regarding the timing of liver transplantation. The aim of this study is to retrospectively evaluate the results of patients who underwent liver transplantation due to mushroom poisoning.